Using modeling techniques to improve information opportunities flaw method detection for heterogeneous materials, based on the phenomenon of mechanoelectrical transformations - Utsyn G. E. Grigoriy Evgenievich (Физические методы в науке и технике, 2014)
Заглавие с титульного экрана